PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI PECAHAN UNTUK SISWA KELAS IV SD NEGERI 38 KURANJI - Zulfa Amrina; Daswarman Daswarman; Srilina Arifin (Program Studi PGSD FKIP Universitas Bung Hatta, 2020)
This study aims to produce a mathematics learning module based on a scientific approach in grade IV SD Negeri 38 Kuranji that meets the criteria of being valid, practical, and effective. This type of research is the researchs and development. The research model of development used is the 4-D model of development which define, design, develop, and disseminate. This research was conducted in the even semester of the 2019/2020 school year. Research instruments include validation sheets, practicality sheets (teacher and student response questionnaires) and effectiveness sheets (pre-test and post- test questions). In the validation process, the module is validated by 1 material expert, 1 design expert and 1 linguist. In the practicality process, the module was tried out by 1 teacher and 23 students. Based on this research, development scientifically based approach to learning mathematics in fourth grade produced modules that meet the criteria for very valid with a percentage of 90.29% votes, meet practical criteria with a percentage of 85.66% and meet the criteria of high effectiveness with percentages of 0, 71. So, it can be concluded that the Mathematics learning module based on the scientific approach in grade IV SD is valid, practical and effective as a resource in learning Mathematics in grade IV SD (Elementary School).